Leukotriene receptor antagonists versus placebo in adults and adolescents with asthma: a systematic review and meta-analysis. - Miligkos, Michail. (2017)
Abstract: Background: Leukotriene receptor antagonists (LTRAs) are recommended as alternative treatment in patients with mild asthma, but their relative effect compared with placebo is unknown. Objective: To determine the benefits and harms of LTRAs compared with placebo in adults and adolescents with asthma. Data sources: MEDLINE and the Cochrane Central Register of Controlled Trials from inception through December 2012. Study selection: Peer–reviewed, English–language, randomized controlled trials ( ≥ 4 weeks in duration) in patients with asthma that reported the effect of LTRAs versus placebo on measures of asthma control. Data extraction: Data on the study population, interventions, outcome measures, adverse events, and study methodology were extracted by three authors. Data synthesis: Forty seven trials satisfied our eligibility criteria. Random–effects model meta–analyses, random–effects meta–regression, and subgroup analyses were performed. In 9 trials, LTRAs reduced the risk of an exacerbation by 35% (summary risk ratio = 0.65, 95% CI 0.50, 0.84). The effect was more pronounced in studies of shorter duration (p < 0.01). LTRAs significantly increased FEV1 (summary mean difference [MD] from 13 trials= 0.11 liters, 95% CI 0.08, 0.15; summary MD in percent change from 11 trials = 5.95, 95% CI 3.3, 8.6) and FEV1 % predicted (summary MD from 8 trials = 4.2%, 95% CI 1.5, 1.9). Daytime symptoms (summary standardized MD from 14 trials = −0.21, 95% CI −0.37, −0.04), short-acting β2–agonist use (summary MD from 11 trials = −0.65 puffs/day, 95% CI −0.82, −0.49; summary MD in percent change from 8 trials = −16.4, 95% CI −22.4, −10.4), nocturnal awakenings (summary MD from 7 trials= −0.66, 95% CI −1,−0.3), and asthma–specific quality of life (summary standardized MD from 5 trials = 0.13, 95% CI 0.02, 0.2) were also significantly improved compared to placebo. The proportions of patients with adverse events were similar between intervention and comparator groups. Limitations: Variation in definitions and reporting of outcomes, large heterogeneity, and possible selective outcome reporting bias. Conclusion: LTRAs improved asthma control compared to placebo. It remains unclear however, which patients with asthma are more likely to respond to treatment with LTRAs.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Kent.; Committee: Ethan Balk, Christopher Schmid, and Sucharita Kher.; Keyword: Health sciences.